PENGARUH MOTIVASI BELAJAR DAN KESIAPAN BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS XI IPS DI SMA NEGERI 1 KOTA JAMBI - Yani, Yulinda; Sari, Pratiwi Indah (SJEE (Scientific Journals of Economic Education), 2022)
This study aims to: 1) to determine the description of learning motivation, learning readiness, and student learning outcomes in economics class XI social studies at SMA Negeri 1 Jambi City, 2) to determine learning motivation on student learning outcomes in economics class XI subjects. Social Studies at SMA Negeri 1 Jambi City, 3) to determine the effect of learning readiness on student learning outcomes in economics class XI social studies at SMA Negeri 1 Jambi City, 4) to determine the effect of learning motivation and learning readiness on student learning outcomes in subjects economics class XI IPS at SMA Negeri 1 Jambi City. The design in this research is quantitative research, using survey method. The population in this study were students of class XI IPS, with a total sample of 82 students. Meanwhile , the data analysis technique used is multiple linear regression analysis . The results of the data analysis using the multiple regression formula with the help of the SPSS version 21 program were obtained: 1) learning motivation got a respondent's achievement score of 78.08% with a good enough category, learning readiness of respondents' achievement value of 68.28% with a good enough category and learning outcomes student value < 67 is 48.54%, learning outcomes with student scores = 67 are 2.92%, and learning outcomes with student scores > 67 are 48.54% with a fairly good category; 2) there is an effect of learning motivation on learning outcomes of 0.589; 3) there is an effect of learning readiness on learning outcomes of 0.513; 4) there is an effect of motivation and learning readiness on learning outcomes of 0.417 and 0.288, this means that there is a significant influence between learning motivation and learning readiness on learning outcomes of students of class XI social studies at SMA Negeri 1 Jambi City. Keywords: Motivation, Readiness, Learning Outcomes